Ni coated LiH nanoparticles for reversible hydrogen storage - Wang, L.; Quadir, Md Zakaria; Aguey-Zinsou, K. (Elsevier Ltd, 2016)
Lithium is a material of choice for batteries, but it has also the potential to store energy with high density as a hydrogen storage material, i.e. via the formation of its hydride (LiH). However, the high thermodynamic stability of LiH has so far precluded the use of lithium as an effective hydrogen storage material owing the high temperature 700 °C for hydrogen release. Herein, we report on a novel method to enable the reversible storage of hydrogen with lithium under mild conditions of pressure (6 MPa) and temperature (350 °C). Through the catalytic hydrogenation of lithium, LiH particles were restricted to a few nanometres (<4 nm). Further coating with nickel chloride enabled the formation of a Ni shell at the surface of the LiH nanoparticles leading to their effective stabilization for hydrogen release and uptake with fast kinetics - full hydrogen release/uptake was achieved in less than 50 min at 350 °C. This demonstrates that the properties of LiH are particle size dependent and thus offers new avenues to achieve high energy storage lithium based devices. Copyright © 2016, Hydrogen Energy Publications, LLC.